Co-production: towards a utopian approach. Issue 1 (2nd January 2018) - Bell, David M.; Pahl, Kate
Abstract: This article outlines how co-production might be understood as a utopian method, which both attends to and works against dominant inequalities. It suggests that it might be positioned 'within, against, and beyond' current configurations of power in academia and society more broadly. It develops this argument by drawing on recent research funded through the UK's Connected Communities programme, led by the Arts and Humanities Research Council; and by attending to arguments from the field of Utopian Studies. It explores particular issues of power and control within the field of co-production, acknowledging that neoliberalism both constrains and co-opts such practice; and explores methodological and infrastructural issues such that its utopian potential might be realised.